Adnexal masses encountered during cesarean delivery. Issue 2 (14th August 2013) - Baser, Eralp; Erkilinc, Selcuk; Esin, Sertac; Togrul, Cihan; Biberoglu, Ebru; Karaca, Mujdegul Z.; Gungor, Tayfun; Danisman, Nuri
Abstract: Objective: To outline and discuss the clinical features and outcomes of adnexal masses that were treated during cesarean delivery at a tertiary referral hospital located in Ankara, Turkey. Methods: The operating room and pathology department databases for 2007–2012 were retrospectively reviewed for surgically managed adnexal masses during cesarean delivery. Clinicopathologic characteristics and maternal and neonatal outcomes were assessed. Results: Adnexal masses occurred in 151 women (0.3% of all cesarean deliveries). Most (54.9%) masses were incidentally discovered during cesarean delivery. The mean mass size was 5.3 ± 3.7 cm (range, 3–30 cm). The majority (96.7%) of the women underwent excision of the mass and ovarian repair. Most masses were benign, with dermoid cysts constituting the most common diagnosis (23.8%). Rare tumors such as thecoma, hyperreactio luteinalis, hemangioma, and benign Brenner tumor were also encountered. Three (2.0%) women were postoperatively diagnosed with ovarian cancer. Preterm delivery and neonatal intensive care unit admission rates were 15.9% and 11.9%, respectively. There were no serious neonatal morbidities and no neonatal mortality. Conclusion: Adnexal masses encountered during cesarean delivery generally have a favorable prognosis in terms of maternal and fetal outcome.